Macrophthalmus (Macrophthalmus) abbreviatus Manning & Holthuis, 1981, a new natural host for Hematodinium perezi infection - Liu, Zhengmin; Xie, Guosi; Wang, Hailiang; Li, Xinshu; Wan, Xiaoyuan; Li, Ang; Zhou, Liqing; Shi, Chengyin; Zhang, Qingli; Huang, Jie (Frontiers in Cellular and Infection Microbiology, 2024)
Recent reports have shown that wild crabs may be important hosts involved in the transmission and spread of the parasitic Hematodinium in cultured marine crustaceans.Therefore, monitoring the prevalence of Hematodinium infections in wild crabs is necessary to develop effective strategies for the prevention and control of Hematodinium disease. Here we report a wild crab species, Macrophthalmus (Macrophthalmus) abbreviatus Manning & Holthuis, 1981, as a new natural host for Hematodinium sp. infection. It is one of the common wild crab species dwelling in the ponds or waterways connected to the polyculture ponds located on the coast of Rizhao or Weifang, Shandong Peninsula, China. According to the results of PCR detection and phylogenetic analysis targeting the internal transcribed spacer 1 (ITS 1) region, these Hematodinium sp. isolates were identified as H. perezi and fell into the genotype II category within H. perezi. A high monthly prevalence of H. perezi infection was observed during the 2021-2022 field survey, ranging from 33.3% to 90.6% in M. abbreviatus originating from Weifang (n=304 wild crabs) and from 53.6% to 92.9% in those from Rizhao (n=42 wild crabs). Artificial inoculation infection experiments demonstrated that M. abbreviatus could be infected by H. perezi, and massive Hematodinium cells and typical histopathological changes were observed in the hepatopancreas and gill tissues of the infected crabs. To our knowledge, this is the first report of M. abbreviatus as a new natural host for H. perezi infection. Results in the present study extend the known host spectrum for this emerging parasite pathogen, and also provide valuable information for epidemic surveillance of the Hematodinium disease as well.